The Existence and Stability of Solutions for Vector Quasiequilibrium Problems in Topological Order Spaces - Qi-Qing Song (Journal of Applied Mathematics)
In a topological sup-semilattice, we established a new existence result for vector quasiequilibrium problems. By the analysis of essential stabilities of maximal elements in a topological sup-semilattice, we prove that for solutions of each vector quasi-equilibrium problem, there exists a connected minimal essential set which can resist the perturbation of the vector quasi-equilibrium problem.